Knowledge and awareness of HPV virus and HPV vaccine among medical students - J. C., Malavika; Hegde, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical cancer remains one of the major public health problems in India. India accounts for nearly one third of global cancer deaths with cumulative risk of developing cancer cervix is 1.6% and cumulative death risk is 1%. Infection with human papilloma virus increases the risk of acquisition of cervical cancer. High risk HPV such as HPV 16 and 18 are commonly associated with invasive cervical cancer. Implementation of HPV vaccination is a primary prevention strategy. Methods: A cross-sectional study was conducted at SSIMS and RC, Davangere, Karnataka., including the first year medical students (148 students recruited). A 32-point questionnaire was administered to assess the knowledge, attitude and awareness regarding HPV virus and vaccination. The data was entered in Microsoft Excel and analysed using EpiInfo software. Results: Majority of the students were aware about the virus and the infection it causes. Only 50% of the students were aware of spectrum of malignancies HPV causes. 50% of the participants opined that HPV vaccination protects against cervical cancer. Students were more sceptical about the side effects caused by the vaccine. Only 35% of the students knew the right time to vaccinate. Almost all participants strongly felt the need to spread the information regarding HPV infection across the general public. Conclusions: Knowledge about HPV virus such as its role in causing cancer, subtypes, pathogenic mechanism and HPV vaccination is crucial. Being future physicians and their responsibility towards community, medical students are expected to know the basics about HPV virus and vaccine.